Analysis of the Principles of Modern Intensive Methods - Rakhimova Muhabbat Ergashevna (Peerian Journals Publishing, 2022)
This article defines the principles and their impact on foreign language learners through an intensive teaching methodology
Keywords: principle; integral; suggestive; concentration